Phytochemical Profile and Biological Effects of Spruce (Picea abies) Bark Subjected to Ultrasound Assisted and Microwave-Assisted Extractions - Adrian Nisca; Ruxandra Ștefănescu; Diana Ionela Stegăruș; Anca Delia Mare; Lenard Farczadi; Corneliu Tanase (Plants, 2021)
The bark of various tree species is a byproduct of the forestry industry that is not used at its full potential, considering the wide range of phytochemicals that are contained in these vegetal matrices and the health benefits that these compounds could provide for society. Our goal was to assess and compare the phytochemical composition of some hydroalcoholic spruce (Picea abies) bark extracts attained by ultrasound assisted extraction (UAE) and microwave-assisted extraction (MAE) and their antioxidant and antibacterial effects. The levels of total phenolics and tannins in the bark extracts were determined using methods based on the Folin–Ciocâlteu reagent, while specific phenolic and volatile compounds were identified and quantified using an UPLC-PDA method and a GC-FID method, respectively. After the chemical composition assessment, the antioxidant capacity (AC) was evaluated by measuring the scavenging ability against two free radicals (DPPH and ABTS). The minimum inhibitory concentration (MIC) was determined to assess the antibacterial activity of the extracts. The results indicated that the extracts produced by UAE had higher contents of polyphenols and tannins and also a higher content of the main phenolic compounds identified, catechin and epicatechin, compared to the MAE extracts. In contrast the highest content of volatile terpenoids (mainly α- and β-pinene) was found in the MAE extracts. All of the tested extracts exhibited relatively high antioxidant activities (especially the UAE extracts) and low MICs against Gram-positive bacteria but were mildly efficient against Gram-negative bacteria. These findings show that the spruce bark might be an important source of bioactive compounds that can be easily extracted from these industrial secondary products. Various uses of this vegetal material may emerge, due to its antioxidant and antibacterial effects.